PENGARUH BENTUK RUANG KOMUNAL COHOUSING TERHADAP PERILAKU ANGGOTA KOMUNITASNYA EFFECTS OF COHOUSING COMMUNAL ROOM’S SHAPE ON THE BEHAVIOUR OF ITS COMMUNITY MEMBERS - Annisa Nussaiba Azzahra; Cama Juli Rianingrum; Ahadiat Joedawinata (Universitas Trisakti, 2021)
AbstractHuman behavior is defined as an effort made by humans because of a need. A human being is said tohave reasonable behavior if there is an effort to harmonize the role of humans on their needs as individualbeings and also as social beings. Spatial Language Theory explains that human reputation and the waythey get along with other humans are the most powerful things that humans feel. Therefore, the way inwhich a space facilitates or hinders this behavior is the most important thing to consider when observingand designing a space. In line with this theory, the theory of 9 Guiding Elements of Design explains thatthe ideal design of a space is carried out through a process of analysis of the Needs and Wills of the spaceuser. This study aims to identify the effect of Cohousing Communal Space in Kampung Communitiesin East Java on the Behavior of Community Members. The qualitative narrative research method waschosen to examine: Primary Data Sources, in the form of direct observations and interviews conductedby research assistants on the research object, and Secondary Data Sources, namely a collection ofvarious literature studies and documentation related to the research object. From the results of theanalysis carried out on the elements: User-Maker of Sapce, Content of Space and Shaper of Space, it canbe concluded that there are three Cohousing indicators found in the Kampung Community, namely:Sense of Safety, Contractual Character, and Contractual Community. There is a match between thebehavior of community members with the physical and social background in the village community.The behavior of the Village Community Members is formed because of the Communal Activities thatare carried out repeatedly in the Communal Space within the Village Community. This is due to theHomogeneous Needs of Community Members.Keywords: cohousing, communal space, 9 guiding elements of design, the language of space, humanbehaviorAbstrakPerilaku Manusia didefinisikan sebagai sebuah usaha yang dilakukan oleh manusiadikarenakan adanya kebutuhan. Seorang manusia dikatakan memiliki perilaku wajarapabila didalamnya terdapat upaya penyelarasan peran manusia atas kebutuhan merekasebagai makhluk individu dan juga sebagai makhluk sosial. Teori Bahasa Ruang menjelaskanbahwasanya reputasi manusia dan cara mereka bergaul dengan manusia lain adalah halpaling kuat yang dirasakan oleh manusia. Oleh karena itu, cara bagaimana sebuah ruangmemfasilitasi atau menghalangi perilaku ini menjadi sebuah hal yang paling diperhatikanketika melakukan pengamatan dan perancangan ruang. Sejalan dengan teori tersebut, dalamteori 9 Unsur Pemandu Desain dijelaskan bahwasanya perancangan sebuah ruang secaraideal dilakukan melalui proses analisa terhadap faktor Needs dan Wills dari pengguna ruang.Penelitian ini bertujuan untuk mengidentifikasi pengaruh Ruang Komunal Cohousing padaKomunitas Kampung di Jawa Timur terhadap Perilaku Anggota Komunitasnya. Metodepenelitian deskriptif kualitatif dipilih untuk mengkaji: Sumber Data Primer, berupa hasilobservGasi langsung dan wawancara yang dilakukan oleh asisten peneliti terhadap objek penelitian, serta Sumber Data Sekunder, yaitu kumpulan berbagai studi literatur dan dokumentasi terkait objek penelitian. Dari hasil analisa yang dilakukan terhadap unsur-unsur:Pengguna-Pembuat Ruang, Muatan Ruang, dan Pembentuk Ruang dapat disimpulkan bahwaterdapat tiga indikator Cohousing yang ditemukan di dalam Komunitas Kampung, yaitu:Sense of Safety, Contractual Character, dan Contractual Community. Terdapat kesesuaian antaraperilaku anggota komunitas dengan latar fisik dan latar sosial di dalam komunitas kampung.Perilaku Anggota Komunitas Kampung terbentuk karena adanya Aktifitas Komunal yangdilakukan secara berulang pada Ruang Komunal di dalam Komunitas Kampung. Hal inidikarenakan Kebutuhan Anggota Komunitas yang bersifat Homogen.Kata kunci: cohousing, ruang komunal, 9 unsur pemandu, the language of space, perilaku manusia